Optimasi Pengaturan Lampu Lalu Lintas dengan Menggunakan Metode Webster (Studi Kasus Persimpangan Jalan Malino) - Sahlan Sidjara; Adinda Maghfirah Tiham; Syamsuddin Mas’ud (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2026)
The increasing number of vehicles in Gowa Regency causes congestion at the Malino Road Intersection, triggering long queues and longer travel times, so that signal optimization is needed. This study aims to optimize traffic light duration by combining compatible graphs and the Webster method. The method used is applied research with a quantitative approach, utilizing primary data from field surveys and secondary data from the Transportation Agency. The research was conducted at the Department of Transportation of Gowa Regency and the Department of Mathematics, FMIPA UNM, from April to June 2025. Compatible graphs are used to determine the phase without conflict, while the Webster method is applied to calculate the optimum cycle time and the division of green and red times based on traffic load. The results show that all flows conflict with each other so that three phases are required with an optimum cycle time of 171 seconds. After optimization, there is an increase in green time on several approaches, especially Jalan Malino and Usman Salengke Selatan, as well as adjustments to red time. Overall, this arrangement improves intersection efficiency and smooths traffic flow although at some points there is an increase in waiting time that remains optimal.